Conventional Mercury Penetration and Constant Velocity Mercury Penetration Experiments Are Used to Quantitatively Characterize the Difference in Micropore Structure in Low Permeability Reservoirs and Its Influence on Movable Fluid Saturation. (19th April 2023) - Yuan, Kaitao; Li, Yan; Shi, Tiaotiao; Huang, Husheng; Li, Yanfei; He, Minglei
Abstract : There are many research methods and experimental means for quantitative and semiquantitative evaluation of low permeability reservoirs. Generally, people do not use a single means to study them but use a variety of experimental means to verify and complement each other. Conventional mercury penetration and constant velocity mercury penetration are two important experimental methods for the quantitative evaluation of tight reservoirs. The micro characteristic parameters of reservoirs obtained by them are quite different, which bring some difficulties to people's research. This paper first analyzes the reasons for the differences between the two from the aspects of experimental theory and model, experimental conditions, and experimental process. Taking C 6 and C 7 reservoirs in Ordos Basin as an example, a total of 13 representative pairs of samples were selected to analyze the difference in capillary pressure curve shape and pore throat distribution characteristics between the two experiments and to clarify the reasons for the difference in microscopic pore characteristic parameters measured by the two experiments. Finally, the correlation between the microscopic pore characteristic parameters and the movable fluid saturation parameters is analyzed. The results show that the theoretical model of conventional mercury penetration experiment is a capillary tube bundle model with different radii. The maximum injection pressure of experimental mercury is high and the experimental speed is fast. The theoretical model of constant velocity mercury penetration experiment is the pore and throat capillary model with different radii. The maximum injection pressure is low, the experimental speed is very slow, and the process is quasistatic. The parameters such as displacement pressure, total mercury saturation, and separation coefficient obtained by the latter are smaller than those measured by the former; however, the maximum throat radius, average throat radius, and other parameters obtained by the latter are larger than those measured by the former. According to the correlation chart drawn, it can be concluded that the correlation between the microscopic pore throat characteristic parameters and the movable fluid saturation in the constant velocity mercury penetration experiment is better than that in the conventional mercury penetration experiment. The influencing factors mainly include permeability, porosity, displacement pressure, maximum pore throat radius, and sorting coefficient. The maximum mercury injection saturation has little correlation.